Tinjauan Literatur : Praktik Akuntansi Biru dalam Pengelolaan Karbon Pesisisr di Indonesia dan Malaysia - Rukmana, Risa; Muflikhah, Itsna (Universitas Islam Negeri Alauddin Makassar, 2026)
Increasingly intense climate change has made blue carbon ecosystems increasingly important in carbon management strategies worldwide. The purpose of this systematic literature review is to combine theoretical and empirical studies on blue accounting practices in coastal carbon management in Malaysia and Indonesia. The study uses the PRISMA approach to identify factors that support and hinder the implementation of blue accounting, evaluate the effectiveness of various methodologies, and examine how carbon management practices in coastal ecosystems interact with socio-economic, environmental, and policy factors. Four key themes emerge from the review: conceptualization and blue accounting frameworks; technical and methodological approaches; integration of institutions, policies, and governance; and economic valuation and market-based tools. The results indicate that Indonesia and Malaysia have significant coastal carbon potential. This study contributes to the development of a more practical, relevant, and comparative blue accounting framework for coastal ecosystem management policies in Southeast Asia.